Transplantasi Pengaturan Larangan Praktik Female Genital Mutilation melalui Studi Perbandingan Indonesia dengan Mesir - Yulita Dwi Pratiwi (Badan Strategi Kebijakan Hukum, 2022)
Efforts to eliminate and prevent the practice of P2GP/FGM which are considered human rights violations against women are carried out by banning P2GP/FGM in several countries, one of which is Egypt. Meanwhile, there is no regulation or policy to stop P2GP/FGM in Indonesia. Seeing the decline in the prevalence of FGM practices in Egypt, the authors are interested in analyzing the transplantation of P2GP/FGM prohibition settings through a comparative study of Indonesian and Egyptian laws. This research is normative legal research with a conceptual approach and comparative law. Comparative law studies are conducted to get an overview of solutions to the same problems in other countries. The practice of P2GP/FGM in both Indonesia and Egypt is based on ancient traditions and not for medical or religious purposes. The striking difference between the two countries in eliminating FGM practices is the commitment to regulate FGM in legal instruments in their countries. Therefore, in dealing with problems with the same root cause, Indonesia can refer to the same solution, namely by formulating legal instruments regarding P2GP/FGM as a criminal act by carrying out legal transplants adapted to the ideals of the Indonesian legal state.